PENGARUH MODEL PEMBELAJARAN INSTAD TERHADAP PRESTASI BELAJAR IPA SISWA KELAS V SD MUHAMMADIYAH 1 WONOPETI KULON PROGO - Retno Utaminingsih; Mawan Akhir Riwanto (Universitas Sarjanawiyata Tamansiswa, 2022)
Science learning requires a learning model that makes it easier and motivates elementary school students in learning. Based on that, this study aims to determine the effect of the InSTAD learning model on science learning achievement. The research method used is quasi-experimental with the Nonequivalent Control Group Design. This research was conducted in the fifth grade of SD Muhammadiyah 1 Wonopeti Kulon Progo. Data collection techniques using test techniques and documentation techniques. The data analysis technique used the t-test before the data was analyzed, the analysis prerequisite test was carried out, namely the distribution normality test using Chi-Square and the homogeneity test of variance using the F-test. In this study obtained tcount= 4.419 with p = 0.000. Because the p-value ≤ 0.01, it can be concluded that there is a very significant difference in the science learning achievement of fifth-grade students of SD Muhammadiyah 1 Wonopeti Kulonprogo for the 2018/2019 academic year between learning using the InSTAD learning model and learning using the expository learning model. The mean score of science learning achievement in the experimental class using the InSTAD learning model is 15,483 and the mean score for science learning achievement in the control class using the expository learning model is 13,136. Because the mean score of science learning achievement using the InSTAD learning model is higher than the mean score of science learning achievement using the expository learning model, there is an effect of the InSTAD learning model on the science learning achievement of fifth grade students at SD Muhammadiyah 1 Wonopeti Kulonprogo for the 2018/2019 academic year.